Peace movements and pacifism after September 11 /c [edited by] Shin Chiba, Thomas J. Schoenbaum - Chiba, Shin 1949-; Schoenbaum, Thomas J. (Edward Elgar, 2008)
Noted international scholars present Japanese and East Asian perspectives on how the attacks of September 11, 2001 in the United States changed prospects for international peace. The authors show that the events, while serious, need not lead to perpetual war and the end for hopes of peace in the twenty-first century. Because East Asia has not been preoccupied with the ongoing conflicts in the Middle East, their views can serve as a balance to the 'war' on terror declared in the United States